Impact of smoking status at diagnosis on oncological outcomes of upper-tract urothelial carcinoma - Hongda Zhao; Kang Liu; Alfonso Crisci; Ed te Slaa; Tomonori Habuchi; Murat Akand; Chi Fai Ng; Pilar Laguna; Jeremy Yuen-Chun Teoh; Jean de la Rosette (Therapeutic Advances in Urology)
Background: The evidence supporting personalized surveillance strategies for upper-tract urothelial carcinoma (UTUC) remains limited. This study seeks to explore how smoking habits influence the oncological outcomes of UTUC Methods: Data on disease characteristics from UTUC patients were gathered prospectively. Recurrence-free survival was the primary outcome measured. Patients were stratified based on smoking status for Kaplan–Meier and multivariable Cox regression analyses. Results: A total of 1952 patients were involved, including 684 (35%) patients who never smoked, 572 (29%) that were ex-smokers, and 696 (36%) that were current smokers. For female patients, most of them were nonsmokers ( n  = 328). Current smokers were significantly younger and had higher American Society of Anesthesiologist (ASA) scores and Charlson Comorbidity Index. A total of 19.9% ( n  = 236) of patients developed tumor recurrence. Kaplan–Meier analyses showed that smoking status was associated with a greater likelihood of urothelial carcinoma recurrence ( p  = 0.011) and intravesical recurrence ( p  = 0.021). The multivariable Cox regression analysis identified the smoking status as an independent risk factor for urothelial carcinoma recurrence ( p  = 0.046). When compared with former smokers, current smokers showed a higher urothelial carcinoma recurrence ( p  = 0.016) and intravesical recurrence ( p  = 0.006). Conclusion: Smoking at the time of diagnosis was significantly associated with an increased risk of tumor recurrence in the bladder but not significantly in the upper urinary tract. This study confirms that cumulative smoking exposure accelerates the risk of tumor recurrence and underlines the importance of smoking cessation. Trial registration: NCT02281188.